1990
DOI: 10.1165/ajrcmb/2.5.413
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Dissolution of Uniform Cobalt Oxide Particles by Human and Canine Alveolar Macrophages

Abstract: Intracellular dissolution of inhaled particles is an important pathway of clearance of potentially toxic materials. To study this process, monolayers of human and canine alveolar macrophages (AM) were maintained alive and functional in vitro for more than 2 wk. Complete phagocytosis of moderately soluble, monodisperse 57Co3O4 test particles of four different sizes was obtained by optimizing the cell density of the monolayer and the particle-to-cell ratio. The fraction of the initial particle mass that was solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 31 publications
0
48
0
2
Order By: Relevance
“…In a more quantitative approach, the intracellular dissolution rates of monodisperse, porous Co304 particles with different specific surface areas were determined in cultured AM from man and dogs (48)(49)(50)(51) and in AM of man, rats, and baboons (52) using slightly different methods. In the latter study, 260-mL culture flasks were used to culture all the AM together, and in the former study, the cells were incubated in 96-well cell culture plates, which allowed additional cell function tests in separate wells to be conducted during the entire incubation time.…”
Section: Intracellular Particle Dissolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more quantitative approach, the intracellular dissolution rates of monodisperse, porous Co304 particles with different specific surface areas were determined in cultured AM from man and dogs (48)(49)(50)(51) and in AM of man, rats, and baboons (52) using slightly different methods. In the latter study, 260-mL culture flasks were used to culture all the AM together, and in the former study, the cells were incubated in 96-well cell culture plates, which allowed additional cell function tests in separate wells to be conducted during the entire incubation time.…”
Section: Intracellular Particle Dissolutionmentioning
confidence: 99%
“…various time points during 2 weeks ofincubation (50). Because the integrity and function of the cultured AM is another essential condition for this assay during the 2 weeks ofincubation, cell viability and phagocytic function were monitored at each sampling time to discard results from malfunctioning cell cultures.…”
Section: Intracellular Particle Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies emphasize the difference between the phagosome compartment of macrophages and epithelial cells, in particular their pH. Certain in vitro studies (45,46) have shown a good correlation with in vivo studies. However, in one study, using an acellular dissolution system (45) Certain factors have to be considered for the development of in vitro cell systemsthe particle dimensions, the nature of culture media, and the cell viability.…”
Section: Chemical Biopersisencementioning
confidence: 80%
“…Particles are not only ingested but undergo gradual dissolution within the phagolysosomes of macrophages (1). The …”
Section: Introductionmentioning
confidence: 99%